(untitled) (Avocetta, 2019)
Italian Ornithological Commission (COI) - Report 28. This report refers to records from 2018, with the addition of a number of records from previous years which were submitted more recently. For each species, the records are listed by date and information is given as follows: Italian and scientific name, the number of accepted records pre- and post-1950 (the numbers in this abstract refer to the total number of records), number of individuals if more than one, age or plumage and sex if known, location, date, names of observers, and documentation (photograph, sound recording, skin etc.). Taxonomy follow the new CISO-COI Italian Checklist (http://ciso-coi.it/commissione-ornitologica-italiana), which also includes subspecies and follows the taxonomy adopted by the HBW-BirdLife Checklist, as decided by the CISO council in 2018. A total of 41 submissions involving 29 taxa were assessed. The following 28 records, involving 22 taxa, were accepted, including 3 first records for Italy (Cat. AERC: A – COI List 1A, 1B): Oriental Turtle Dove Streptopelia orientalis cf. meena (Trentino - Alto Adige 2017; 2nd record for Italy); Yellow-billed Loon Gavia adamsii (Friuli Venezia Giulia 2018; 6th record); Brown Booby Sula leucogaster (Tuscany 2017; 4th record); Pacific Golden Plover Pluvialis fulva (Campania, 11th record); White-tailed Lapwing Vanellus leucurus (Emilia-Romagna 2018; 5th record); Least Sandpiper Calidris minutilla (Latium 2015; 2nd record); White-rumped Sandpiper Calidris fuscicollis (Emilia-Romagna 2018; 2nd record); Black-winged Pratincole Glareola nordmanni (Friuli Venezia Giulia 2018; 7th record); Heuglin’s Gull Larus fuscus heuglini (Abruzzo 2018; 3rd record); Guillemot Uria aalge albionis (Tuscany 2018; 2nd record); Blue-cheeked Bee-eater Merops persicus (Apulia 2018; 10th record); Isabelline Shrike Lanius isabellinus (Sicily 2017; 8th record); Elegant Grey Shrike Lanius excubitor elegans (Sicily 2017; 7th record); Brown-necked Raven Corvus ruficollis (Sicily 2017; first record for Italy); Bar-tailed Lark Ammomanes cinctura arenicola (Sicily 2018; 4th record); Dusky Warbler Phylloscopus fuscatus (five records: Sicily 2015, 2015, 2016, 2017; Calabria 2017; 10th-12th records and 14th-15th records); Greenish Warbler Phylloscopus trochiloides viridanus (Latium 2018; 2nd record); Asian Desert Warbler Sylvia nana (Apulia 2018; first record); Moussier’s Redstart Phoenicurus moussieri (three records: Sicily 2015, 2015, 2016; 10th-12th records); Caspian Stonechat Saxicola torquatus hemprichii (Campania 2018; 3rd record); Black-throated Accentor Prunella atrogularis (Apulia 2014; first record); Blyth’s Pipit Anthus godlewskii (Sicily 2018, 2nd record). The following record was accepted at the Genus level only (COI List 1C): Isabelline/Red-tailed Shrike Lanius isabellinus/phoenicuroides (Sicily 2011; 4th record). The following records were accepted as birds with uncertain natural origin (possibly ship-assisted: COI List 2A): Pied Crow Corvus albus (two records: Apulia 2008; Sicily 2018; 1st and 2nd records). The following record was accepted as first breeding case for Italy (COI List 6A): Booted Eagle Hieraetus pennatus (Basilicata 2018). Rejected records (COI List 5A, 5B) were: Eastern Cattle Egret Bubulcus coromandus (Veneto 2013); Least Sandpiper Calidris bairdii (Emilia Romagna 2016); Isabelline Shrike Lanius isabellinus (Latium 2008); Iberian Pied Flycatcher Ficedula hypoleuca iberiae (Latium 2018); Atlas Pied Flycatcher Ficedula hypoleuca speculigera (Latium 2018); White-crowned Wheatear Oenanthe leucopyga (Tuscany 2018). Two records are still pending and were not included here.